2016
DOI: 10.1038/bjc.2016.244
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: miR-23a promotes IKKα expression but suppresses ST7L expression to contribute to the malignancy of epithelial ovarian cancer cells

Abstract: Background:Dysregulation of microRNAs (miRNAs) has been found in human epithelial ovarian cancer (EOC). However, the role and mechanism of action of miR-23a in EOC remain unclear.Methods:The roles of miR-23a, IKKα, and ST7L in EOC were determined by MTT, colony formation, wounding healing, transwell, flow cytometry, immunofluorescence, RT–qPCR, and western blotting experiments. miR-23a target genes were validated by EGFP reporter assays, RT–qPCR, and western blotting analysis.Results:miR-23a is upregulated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Inactivation of Wnt/β-catenin signaling caused by ST7L by repressing β-catenin expression could explain this phenomenon to a certain extent in epithelial ovarian cancer ( 21 ). To address these issues, the expression of Wnt genes and the activity of β-catenin were analyzed in the context of miR-378 overexpression or miR-378 overexpression in conjunction with pST7L in cervical cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inactivation of Wnt/β-catenin signaling caused by ST7L by repressing β-catenin expression could explain this phenomenon to a certain extent in epithelial ovarian cancer ( 21 ). To address these issues, the expression of Wnt genes and the activity of β-catenin were analyzed in the context of miR-378 overexpression or miR-378 overexpression in conjunction with pST7L in cervical cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Suppression of tumorigenicity 7-like (ST7L) was identified based on its similarity to the ST7 tumor suppressor gene ( 18 ). ST7L is downregulated in different cancers, including gastric cancer ( 19 ), glioma ( 20 ), ovarian cancer ( 21 ) and hepatocellular carcinoma ( 22 ). For example, Chen et al ( 20 ) demonstrated that the deletion of miR-24 suppressed β-catenin/Tcf-4 transcription activity by targeting ST7L in glioma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, miR-23a accelerates autophagy and increases survival and migration of breast cancer cells by targeting XIAP (27). A previous study concluded that miR-23a up-regulates IKK alpha expression while down-regulating the expression of ST7L expression, ultimately enhancing the malignant phenotypes of epithelial ovarian cancer cells (28). The apoptosis of GC cells can be inhibited by miR-23a by down-regulating PPP2R5E (29).…”
Section: Discussionmentioning
confidence: 99%
“…An example of miRNA that acting oncogene is miR‐23 that targets IKKa (IkA kinase, catalytic subunit of NF‐kB) and STL7 (Suppression of tumorigenicity 7 like, similarity to the ST7 tumor‐suppressor gene) , thus contributing to the malignancy of epithelial ovarian cancer (EOC) cells. The proliferation, migration, and invasion of EOC cells are increased by IKKa and inhibited by STL7 .…”
Section: Introductionmentioning
confidence: 98%